Effect of injection barrier height on charge transport under bipolar injection. (9th August 2018) - Meftali, Nadia; Bouazabia, Slimane; Fofana, Issouf; El Maouhab, Ali
Abstract: In this paper, a numerical model describing the transient phenomena of electric charge in a dielectric because of a double injection at 2 electrodes is proposed. The mathematical model and the methods for its resolution are presented step by step. Thus, the Schottky equation is used to describe the injection of negative and positive charges from the cathode and anode respectively. The equations governing the conduction are the current equation and the Poisson equation coupled to the continuity equation. The adopted model uses the applied voltage instead of the applied electric field. The Poisson equation is solved by finite differences using the Thomas algorithm and the continuity equation by Euler's method. The Thomas algorithm reduces considerably the execution time compared to iterative methods. The time step is not constant; it is calculated from the speed of the charges front. The results show that the established model and the method of resolution reproduce correctly the behaviour of the system under a high voltage. It shows also that knowing the injection barrier height can be used to predict the behaviour of the dielectric under electrical stress. The developed model is a tool for describing the behaviour of the charges for a bipolar injection.